The prevalence of functional disability and associated factors among older adults living in Bahir Dar City, Northwest, Ethiopia: a community-based cross-sectional study - Yihenew, Addisu; Ejigu Anteneh, Yeshambel; Miheret, Tewodros; Gobezie, Melese; Eriku, Getachew Azeze; Yimer Shibabaw, Yadelew; Kassa, Tesfa (Frontiers in Public Health, 2024)
Background The limitation of carry out everyday activities independently is a common experience for older adults with functional disabilities, which can hurt their overall well-being. Unfortunately, there is still a dearth of evidence about how common it is among older adults, especially in low-and middle-income countries like Ethiopia. Therefore, the study aimed to assess the prevalence and associated factors of functional disability among older adults living in Bahir Dar city, Northwest, Ethiopia, 2023. Method A community-based cross-sectional study was conducted among older adults (≥60 years) living in Bahir Dar city, Northwest, Ethiopia. A total of 598 study participants were included using a multistage sampling technique. Data were collected through interviewer-administered questionnaires. Barthel Index (BI) was used to assess the functional capacity of older adults which comprises 10 items. The total score ranges from 0 to 100. Variables significant in bivariable analysis were entered into multivariable logistic regression analysis. A p < 0.05 was considered statistically significant in the final logistic regression model. Results Among the 598 participants studied, the overall prevalence of functional disability was 29.6 (95% CI: 26.0–33.4). Older age (≥70 years) {adjusted odds ratio(AOR: 2.24; 95% CI: 1.03–4.88)}, comorbidity (AOR: 2.96; 95% CI: 1.47–5.94), physically inactive (AOR: 2.42; 95% CI: 1.18–4.96), one and more drug users (AOR: 3.61; 95% CI: 2.12–6.15), cognitive impairment (AOR: 3.66; 95% CI: 2.26–4.93) and depression (AOR: 1.70; 95% CI: 1.08–2.68) were found significant associated factors of functional disabilities among older adults. Conclusion This study found that nearly one-third of older adults had functional disabilities. Functional disability was significantly associated with factors such as increasing age, presence of comorbidities, being physically inactive, one and more drug users, who developed cognitive impairment, and having depression symptoms. Proactive measures need to be initiated to ensure proper care and support of functionally disabled individuals, especially targeting vulnerable groups identified in this study.